De intrede van Multatuli in Hongarije - Gera, Judit (Department of Dutch and South African Studies, Faculty of English, 2013)
This article reflects on the importance and nature of cultural transfer studies. Cultural transfer implies a dynamic meeting of cultures which always happens in concrete political, historical and sociocultural contexts. I argue therefore that political aspects and the concept of emancipation play a crucial role in this type of research. After sketching the reception of one of the best-known Dutch authors Multatuli (1820-1877) in Germany, Czechoslovakia and Poland I introduce the most important elements of the Hungarian reception. I focus not only on the role of the socio-cultural background of the translator but also on the political, historical and socio-cultural context of Hungary at the beginning of the twentieth century. In the end I demonstrate parallels in the reception of Multatuli in Central Europe at the last turn of the century.
Keywords: cultural transfer; reception studies; translation; context; Multatuli